Clustering European Welfare Systems through a Performance Index - ANTONELLI, MARIA ALESSANDRA; DE BONIS, Valeria (2016)
We construct a composite performance indicator to assess the relative performance of welfare policies in the EU countries. We show that the variability of performances cannot be explained only by the amount of resources devoted to social policies, but also by the composition of social expenditure: countries with higher shares of redistributive public expenditure obtain better results in the social sector. This result confirms the association between the type of welfare system, according to the traditional four-way classification, and the performance level. However, considering a more complete set of indicators of the structure of the welfare systems, we find that European countries cannot be grouped according to the traditional classification. Considering expenditure-side indicators and financing-side indicators together, three groups form: one comprising the UK and Iceland, one the Nordic countries and the Netherlands, one the continental (and southern) countries and Ireland.